Rozkład statystyki T-Studenta przy danej wariancji z próby o rozkładzie normalnym - Gardoń, Albert (The distribution of the T-Student’s statistic given the variance from a normal sample, 2011)
It is not so easy to lecture on higher mathematics for economy students. Advanced notions must be often presented for people without an appropriate theoretical background, which forces the teacher to simplify. Unfortunately, the praxis shows that the frontier between a simplification and a factual error is often very subtle and it happens this frontier is sometimes crossed. Such a situation occurs just in the case of the problem, which will be described in this paper. It is a known fact that the so called Student’s T statistics from a normal distributed sample is t-Student distributed, without any doubt. But in handbooks for economy students several authors try to use this statistics for exercises with mathematical tables of the t-Student distribution, ordering a calculation of the probability that the sample average will belong to the given interval, in the case when the theoretical variance is unknown but the sample variance has been calculated. Unfortunately, such a situation has nothing to do with the t-Student distribution and this error is systematically copied in successive handbooks
Didactics of Mathematics, 2011, Nr 8 (12), s. 17-30
Keywords: Student’s T statistics; t-Student distribution; normal distribution